Persentase Motilitas Dan Viabilitas Semen Ayam Bangkok Terekuilibrasi Pada Suhu 5oc - Andi Ainur Prasetyo; Dirwan Muchlis; Nurcholis Nurcholis (Musamus Journal of Livestock Science, 2020)
Research aims to know the quality of spermatozoa bangkok male in diluent in NaCl suplementation red fruit at a temperature ekuilibrasi 5oc. The material of which used in this research was semen bangkok male that which is taken by the use of males or the two females anglers upon a chicken a kind of macho . Long kept the temperature is 5oC 60 minutes with 3 repetitions . The ratio of the dilution semen with diluent 1: 10 . Dependent variable for which a observed promised to supply the volume of , the color of , pH , motility of mass , motility and viability sperm. This layout are complete random desing (CRD) and analysis variety of ( anova ). Research obtained 0,4 ± 0,033, white milk, ph ± 0, 6 and motions of masses of + +/ + + +. The results of the analysis statistics show that long save semen bangkok male 5oc with diluents at a temperature in suplementations red fruit for 60 minutes (P<0.01), However to protect a reduced rate and to motility of viability well. The motility of these 60 minute storage for P0= 8,3%; P18,1 % and P2 7,6% We can conclude that its motility and viability spermatozoa cocks bangkok decline normally along with long kept the 5oC Temperature.